Molecular Interaction of Purple Rice Ferulic Acid and Skin Aging-Related Enzymes - Wijayanti, Ernanin Dyah; Fatchiyah, Fatchiyah; Safitri, Anna; Siswanto, Dian (UI Scholars Hub, 2025)
Purple rice is rich in ferulic acid, a phenolic acid abundant in rice. Ferulic acid (FA) has long been recognized for its anti-oxidant properties, which are linked to its skin anti-aging activity owing to its ability to scavenge free radicals and pro-tect cells from damage. Skin anti-aging activity could be assessed by inhibiting skin aging enzymes. However, there was limited information on the mechanism of FA inhibition of these enzymes. This study focused on the molecular interac-tion between purple rice FA and collagenase or tyrosinase, both with and without their substrates. The interaction be-tween FA (CID 445858), collagenase (2Y6I), tyrosinase (5M8M), collagenase substrate (CID 5486160), and tyrosinase substrate (CID 6057) was docked using Hex 8.0.0 Cuda with the default settings. Discovery Studio 2020 and LigPlot software were used to visualize the docking results. Ascorbic acid (CID 54670067) and kojic acid (CID 3840) were used as positive controls for collagenase and tyrosinase, respectively. Molecular docking revealed that FA formed electro-static, hydrogen, and hydrophobic bonds with all aging enzymes, substrates, and enzyme–substrate complexes. FA could bind to both free enzymes and free substrates, consequently attenuating enzyme–substrate bonding, and preventing the substrate from binding appropriately in its normal position. Molecular dynamics simulations demonstrated that FA formed a stable bond with tyrosinase, similar to kojic acid, although the bond with collagenase was less stable. However, the pattern of each parameter during the simulation was comparable with that of ascorbic acid. The current study indicated that the FA from purple rice had the potential to act as an inhibitor of skin aging en-zymes and could be developed as a skin anti-aging candidate